A world unprepared: Missing skills for development - Sarah Gust; Eric Alan Hanushek; Ludger Woessmann (EconPol Forum, 2024)
Ensuring that all children in the world obtain at least basic skills is paramount for world development. At least two-thirds of the world's youth do not even reach basic skill levels - i.e., the world is short of meeting the Sustainable Development Goal of universal quality education. This is the result of our new study, which combines multiple data sources from international tests to conduct a cross-country analysis of basic skills using a common achievement scale. Skill deficits range from 24 percent in North America and the European Union to 89 percent in South Asia and 94 percent in sub-Saharan Africa. An economic analysis suggests that the world is missing out on over USD 700 trillion in economic output over the remaining century, or 12 percent of future GDP, by failing to reach the goal of global universal basic skills.
Keywords: 330